Relationship Between Energy Protein Consumption Level and Illness History Towards Nutritional Status of Toddlers in The Working Area of Camplong Public Health Center, Kupang Regency - Bait, Chrisna Lodyana Nike; Jutomo, Lewi; Marni, Marni (Timorese Journal of Public Health, 2025)
Nutritional problems are generally caused by energy and protein adequacy rates, lack of public knowledge about nutrition, balanced menus, and the existence of areas with poor nutrition. Factors causing malnutrition in Indonesia can be seen from direct and indirect causes. The direct cause of malnutrition is unbalanced food intake, which has an impact on children's eating patterns and nutritional adequacy. The purpose of this study was to see the relationship between energy protein consumption levels and illness history to nutritional status of toddlers in the working area of ​​Camplong Public Health Center, Kupang Regency. This study is an Observational Analytical study with a cross-sectional design. The population in this study were 145 toddlers in the Camplong Health Center working area, Kupang Regency and the sample used in this study was 58 toddlers in the Camplong Health Center working area, Kupang Regency. The sampling technique used was simple random sampling. The results of this study indicate that there is a relationship between food diversity (p-value = 0.031), Energy intake (p-value = 0.045), Protein intake (p-value = 0.045, and History of magic (p-value = 0.009). While for the variable Frequency of eating (p-value = 0.634) showed no relationship. Suggestions for Health Center Officers so that health workers, especially at the Camplong Health Center, increase counseling to parents of toddlers regarding the importance of diverse food consumption, energy intake, and sufficient protein to support optimal nutritional status in toddlers. Education can be done periodically through Posyandu or home visits. For Parents, pay more attention to the quality of toddler food intake, not only in terms of quantity but also diversity and nutritional content, especially protein and energy. Providing balanced nutritious food and preventing disease can help maintain the nutritional status of toddlers